Responsibilities of certified Public Accountants in Business Accounting Systems Perspective in Fighting Against Corruption - Pardi, Pardi (STIE Surakarta, 2013)
Corruption usually happened in accountancy sector is that accountant receive such as fee or present from the client because of their jobs. (according to the will of the client). Accountants only receive a fee or reward that is not much (small) but can cause major corruption in the business world, corruption in the accounting services sector is also give a very high and low impact on tax revenues. This resulted in the public accounting profession in the public for its image as the offense of public harm. The purpose of this study were (1) to describe the role of Certified Public Accountants in the perspective of the business accounting system for combating corruption. (2) to describe a form of misconduct in the practice of Certified Public Accountants. (3) to determine the professions commitment to eradicate corruption in the Public Accountants. This type of research is descriptive research. The research site is in the public accounting firm tin Surakarta, Manufacturing in Surakarta, Tax Office and the Public in Surakarta . The type of data is primary data. Data collection techniques in the study were interviews, observation and literature study, whereas the data analysis technique is interactive analysis. The results showed that (1) Certified Public Accountants has an active and a passive role in combating corruption. That role effectively because it is supported by the components of the legal system consisting of structural components, and cultural substance (2) the offense in the practice of Certified Public Accountants, among others, (a) report the value of income is much lower than the actual, (b) tax consultant assisted the company of a public accounting firm to change the financial statements for the companys operating expenses could be made much larger than the actual, (c) the taxpayer or the tax that the company bribed officials are not tax-deductible value of the investigation and audit of financial statements, (d) tax payer usually give message to the public accountant office that the operational costs can be neatly arranged in such a way that the company is only subject to the tax rate low (3) The commitment of public accountants in fighting against corruption is the participation of IAI in G20 group, update competencies in enhancing professionalism in order to meet the needs of service users and create a strategic step toward uniformity in the language of accounting for financial reporting in the private sector in Indonesia